2019
DOI: 10.4040/jkan.2019.49.1.104
|View full text |Cite
|
Sign up to set email alerts
|

Latent Class Analysis for Health-Related Quality of Life in the Middle-Aged Male in South Korea

Abstract: This study aimed to identify types of quality of life (QoL) based on the 5 dimensions of EQ-5D and predict factors affecting types of QoL. Methods: This study was a secondary analysis using data from the Korean Health Panel Survey-Ⅱ(2012). Participants were 2,071 middle-aged men who had completed the additional survey in 2012 and the data were analyzed using SPSS 20.0 and Mplus 5.21 for latent analysis. Results: Three latent classes of QoL were identified: serious (2.4% of the sample), threatened (15.5%), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
2
4
0
2
Order By: Relevance
“…In addition, sex, age, activity restriction, and perceived health status influenced the EQ-5D score, regardless of eating alone. These results are in line with previous reports that perceived health status is an important factor in improving QOL [9]. A study analyzing the factors associated with HRQOL by age group [16] reported that sex, perceived health status, stress, and various disease-related factors influence HRQOL and that there were marked differences in QOL according to sex and perceived health status among older adults.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, sex, age, activity restriction, and perceived health status influenced the EQ-5D score, regardless of eating alone. These results are in line with previous reports that perceived health status is an important factor in improving QOL [9]. A study analyzing the factors associated with HRQOL by age group [16] reported that sex, perceived health status, stress, and various disease-related factors influence HRQOL and that there were marked differences in QOL according to sex and perceived health status among older adults.…”
Section: Discussionsupporting
confidence: 91%
“…QOL is a health index influenced not only by one's general wellbeing but also by the severity of disease that encompasses physical, psychological, social, and mental health as well as perceived health status and health behaviors, and it is widely utilized as a health indicator worldwide [9]. While the lifespan in Korea has increased, owing to dramatic social, economic, and medical advances, Koreans' healthy life expectancy-the number of years an individual is expected to live disease-free-is approximately 20 years less than the life expectancy [10].…”
Section: Introductionmentioning
confidence: 99%
“…In Korea, several MetS-related studies have analyzed the Korean National Health and Nutrition Examination Survey (KNHANES) data. However, many of those studies focused on people aged ‡20 years [16][17][18][19] and those in their 40s 20 ; few studies have investigated the data of people aged ‡50 years. 21 The incidence of MetS in men does not differ before and after 50 years of age, but in women, it sharply increases after 50 years.…”
Section: Introductionmentioning
confidence: 99%
“…활동제한은 선행연구들 [13,19,20]에서 건강관련 삶의 질 의 가장 유의한 영향요인으로 파악되어 건강행위 항목으로 포함하 였다. 건강관련 삶의 질에 영향을 미치는 정신건강은 스트레스 [19][20][21], 우울 [13,17,20], 자살충동 [20,27], 좌절감 [20] 2) 대상자의 체질량지수에 따른 건강관련 삶의 질을 파악한다.…”
Section: 체질량지수에 따른 건강관련 삶의 질 영향요인에 대한 선행연구unclassified
“…최근 중년 여성의 고스 트레스군에서는 체질량지수가 건강관련 삶의 질의 유의한 예측인 자로 확인되었지만 [17], 중년을 대상으로 체질량지수에 따른 현황 과 건강관련 삶의 질 연관성 및 건강관련 삶의 질의 영향요인을 포 괄적으로 파악한 연구는 찾아볼 수 없었다. 지금까지 중년을 대상으로 건강관련 삶의 질에 관한 선행연구는 특정 지역이나 임의 표본을 대상 [2,3]으로 하였거나, 전국단위 자료를 이용하여 중년여성 [18][19][20]과 중년남성 [21] 각각을 대상으로 건강관련 삶의 질 영향요인을 파악한 연구가 대부분 이었다. 중년여성의 건강 관련 삶의 질 영향요인은 폐경과 신체활동 [18], 주관적 건강상태와 스 트레스 [19], 건강행위, 건강상태 및 정신건강 [20] 이었으며, 중년남성의 건강관련 삶의 질 잠재유형 분석 연구 [21]에서 사회경제적 특성, 건강 상태, 건강행위 및 부정적 정신건강 등이 삶의 질 예측요인이었다.…”
unclassified